2016
DOI: 10.1007/s11103-016-0510-7
|View full text |Cite
|
Sign up to set email alerts
|

The “putative” role of transcription factors from HlWRKY family in the regulation of the final steps of prenylflavonid and bitter acids biosynthesis in hop (Humulus lupulus L.)

Abstract: Lupulin glands localized in female hop (Humulus lupulus L.) cones are valuable source of bitter acids, essential oils and polyphenols. These compounds are used in brewing industry and are important for biomedical applications. In this study we describe the potential effect of transcription factors from WRKY family in the activation of the final steps of lupulin biosynthesis. In particular, lupulin gland-specific transcription factor HlWRKY1 that shows significant similarity to AtWRKY75, has ability to activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 85 publications
4
28
0
Order By: Relevance
“…In a way similar to BA and terpenoids biosynthesis, 4CL generated from phenylpropanoid biosynthesis pathway condensed with three molecules of malonyl-CoA with the aid of enzyme CHS_H1 to yield the aromatic core of PF [25]. RNA-seq analysis revealed that TFs such as HlbHLH2, HlWDR1, HlWRKY1, HlMYB1, HlMYB2, HlMYB3, HlMYB7, and HlMYB8 [25,26,28] essential for regulating PF biosynthesis were present in LF, BR, and LG transcriptomes, which was in agreement with previous studies that LF contain low but detectable level of PF [9]. Nevertheless, 4.7% (2.076) of the assembled transcripts, 5.2% (1975) LF transcripts, 4.8% (637) BR transcripts, 4.9% (375) LG transcripts were annotated to encode for TFs, which could be classified into 93 TF families, including MYB, bZIP, WRKY, C2H2, and bHLH families.…”
Section: Building a Transcriptome Resource And Gene Annotationmentioning
confidence: 99%
See 3 more Smart Citations
“…In a way similar to BA and terpenoids biosynthesis, 4CL generated from phenylpropanoid biosynthesis pathway condensed with three molecules of malonyl-CoA with the aid of enzyme CHS_H1 to yield the aromatic core of PF [25]. RNA-seq analysis revealed that TFs such as HlbHLH2, HlWDR1, HlWRKY1, HlMYB1, HlMYB2, HlMYB3, HlMYB7, and HlMYB8 [25,26,28] essential for regulating PF biosynthesis were present in LF, BR, and LG transcriptomes, which was in agreement with previous studies that LF contain low but detectable level of PF [9]. Nevertheless, 4.7% (2.076) of the assembled transcripts, 5.2% (1975) LF transcripts, 4.8% (637) BR transcripts, 4.9% (375) LG transcripts were annotated to encode for TFs, which could be classified into 93 TF families, including MYB, bZIP, WRKY, C2H2, and bHLH families.…”
Section: Building a Transcriptome Resource And Gene Annotationmentioning
confidence: 99%
“…The elevated levels of PAL and CHS_H1 in BR and LG compared to LF suggested that redirection of carbon flux toward flavonoid biosynthesis defines the size of the PF, flavonols, and anthocyanin in BR and LG tissues in hop. The branch point metabolite naringenin chalcone, which colimits the flux between PF and flavanols/anthocyanin biosynthetic products is regulated by the downstream enzyme activity and TFs [9,25,26]. The higher transcript levels of OMT, HlPT1 and core TFs of MBW and WW complexes in LG compared to BR and LF suggested thatthe major metabolic flux shift of primary metabolism was towards PF biosynthesis in LG tissues.…”
Section: The Differential Expression Patterns Of Unigenes In Differenmentioning
confidence: 99%
See 2 more Smart Citations
“…(www.preprints.org) | NOT PEER-REVIEWED | Posted: 28 September 2018 doi:10.20944/preprints201809.0553.v1In our study, majority of genes involved in primary and secondary metabolism pathways were fluctuated in response to the CBCVd-infection. At the link between primary and secondary metabolism, phenylalanine ammonia-lyase (PAL) serve as first enzyme which is involved in biosynthesis of secondary metabolites such as flavonoids, anthocyanins, prenylflavonoids, and bitter acids in hop[79].Flavonoids constitute a large group of phenolic secondary metabolites and have been shown to have diverse biological functions such as symbiotic nitrogen fixation, pollination and floral pigmentation defense against different biotic and abiotic stresses etc. [80].…”
mentioning
confidence: 99%